A history of the Arab-Israeli conflict - Bikerton, Ian J. (Routledge, Taylor and Francis Group, 2018)
"Examines the issues and themes that have characterized and defined the conflict over the course of its history, bringing the coverage up to date with a twenty-first-century perspective"--Provided by the publisher.